Sadiria kachinensis (Myrsinoideae, Primulaceae), a new species from Myanmar - Utteridge, Timothy; Armstrong, Kate E.; Yoneda, Kaoru; Tanaka, Nobuyuki (Phytotaxa, 2026)
Sadiria kachinensis from Kachin State, Myanmar is described and illustrated as a species new to science. It is morphologically similar to S. boweri and S. solanifolia but differs in several characters especially the smaller leaves on the vegetative shoots and the flowering branches, larger inflorescences and petals, and smaller sepals. In addition, this new species is compared to S. eugeniifolia var. burmanica, the only other member of Sadiria in Myanmar.